A search for vaccines and therapeutic for dengue: a review - Wahab, H.A.; Yusof, R.; Rahman, N.A. (2007)
Dengue is a serious emerging or re-emerging infectious disease that is endemic in over 100 countries. There has been an estimated of 50 million infection per year globally with more than 2.5 billion people are at risk for epidemic transmission. The major burden for dengue is in the south-east Asia and the western Pacific although there have been increasing reports of this disease in the Americas. This infectious disease is caused by the dengue virus which is a member of the Flaviviridae and is spread by the highly domesticated Aedes aegypti mosquito. There are two principal illnesses associated with dengue which are Dengue Fever (DF) and Dengue Haemorrhagic Fever (DHF). The former is a flu-like illness with symptoms like fever, headaches, joint aches and rashes while the latter is more severe and often fatal complication of DF as a result of the dengue shock syndrome (DSS). To date, there is no licensed vaccine or therapeutic drug available for DF and DHF/DSS, although there have been reports of some vaccine candidates in clinical trials. The treatment for DF and DHF/DSS has only been supportive thus far. This paper discusses the protein of the dengue virus as well as reviews some of the work and strategies that have been carried out in the quest for finding vaccines and therapeutic drugs for dengue, particularly those employing computer-aided approaches.